2018
DOI: 10.1093/ageing/afx198
|View full text |Cite
|
Sign up to set email alerts
|

The barriers and facilitators for recognising distress in people with severe dementia on general hospital wards

Abstract: distress may be a simple and easily identified marker of unmet need in people with dementia in hospital. However, modifiable and unmodifiable barriers are suggested that reduce the chance of distress being identified or acted on. Improving our understanding of how distress is identified in this environment, and in turn developing systems that overcome these barriers, may improve the accuracy with which distress is identified on hospital wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…In review 1, 63 studies were reported in 82 papers. Fourteen studies were represented by more than one paper: nine studies were reported in two papers each; 43,58,59,62,75,76,79,82,89,90,92,95,98,99,102,[109][110][111]113,129 three studies were reported in three papers each; 60,65,66,[72][73][74]84,125 and one study was represented in five papers. [69][70][71]96,114 In review 2, 14 studies were reported in 16 papers: one study was reported in three papers.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…In review 1, 63 studies were reported in 82 papers. Fourteen studies were represented by more than one paper: nine studies were reported in two papers each; 43,58,59,62,75,76,79,82,89,90,92,95,98,99,102,[109][110][111]113,129 three studies were reported in three papers each; 60,65,66,[72][73][74]84,125 and one study was represented in five papers. [69][70][71]96,114 In review 2, 14 studies were reported in 16 papers: one study was reported in three papers.…”
Section: Study Selectionmentioning
confidence: 99%
“…[69][70][71]96,114 In review 2, 14 studies were reported in 16 papers: one study was reported in three papers. 23,87,142 To signify the singular nature of these studies, although we included all the papers in the syntheses, the journal article first published from each study will be cited when reporting number of studies with a particular finding; 43,58,60,62,66,69,73,76,79,82,90,92,99,110 when quoting an extract or reporting specific findings, the paper of origin will be cited.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations